2015
DOI: 10.1016/j.corsci.2015.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of carbon-steel with 2-mercaptobenzimidazole in hydrochloric acid

Abstract: Electrochemical measurements and substrate analysis have been employed to probe the corrosion inhibition performance of 2-mercaptobenzimidazole (MBI) for carbon-steel in 1 M, 0.1 M, and 0.01 M HCl. Data demonstrate that the inhibition efficiency of MBI is essentially independent of HCl concentration. Moreover, it is concluded that the presence of MBI impedes the cathodic reduction of dissolved O 2 to a lesser extent than H + . X-ray photoelectron spectra indicate that substrate termination varies as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…The differences in Ecorr value in Tables S1–S5 are about 40 mV/(Ag/AgCl) relative to the Ecorr in the blank solution, indicating that studied compounds could be regarded as mixed‐type inhibitors . The inhibitors act possibly through simple blocking effect due to adsorption of NTA‐ n , namely reducing the area exposed to corrosive media. It is expected that with the increasing of inhibitor concentration, the coverage ratio (θ) of the inhibitor on the steel surface will become larger, and the uncovered surface (1−θ) will become less, which will interrupt the access of H+ and CI1 to the metal surface .…”
Section: Resultsmentioning
confidence: 94%
“…The differences in Ecorr value in Tables S1–S5 are about 40 mV/(Ag/AgCl) relative to the Ecorr in the blank solution, indicating that studied compounds could be regarded as mixed‐type inhibitors . The inhibitors act possibly through simple blocking effect due to adsorption of NTA‐ n , namely reducing the area exposed to corrosive media. It is expected that with the increasing of inhibitor concentration, the coverage ratio (θ) of the inhibitor on the steel surface will become larger, and the uncovered surface (1−θ) will become less, which will interrupt the access of H+ and CI1 to the metal surface .…”
Section: Resultsmentioning
confidence: 94%
“…Unfortunately, because of the presence of Clions this acid is highly corrosive. The use of organic inhibitors is the most practical and effective method for the protection of ferrous materials [10][11][12][13][14][15][16][17]. Generally, molecules containing nitrogen, sulfur, oxygen and aromatic rings are preferred [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole (BI) and its derivatives were used to inhibit the corrosion of metals in a corrosive medium. [11][12][13][14][15][16][17][18] J. Aljourani et al 11 researched the BI, 2-methylbenzimidazole and 2-mercaptobenzimidazole as corro-sion inhibitors for mild steel in the 1M HCl solution; they found that these inhibitors retarded both the cathodic and anodic processes and that the inhibition efficiency was increased with an inhibitor concentration in the order of 2-mercaptobenzimidazole > 2-methylbenzimidazole > BI. Recently, P. Morales-Gil et al 19 found that the IE of 2-mercaptobenzimidazole for carbon steel in the 1M hydrochloric acid is 99 %, with a concentration of 2 mM.…”
Section: Introductionmentioning
confidence: 99%